2001
DOI: 10.1042/bj3530645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of active-site interactions with tetracoordinate transients in acetylcholinesterase and its mutants

Abstract: The role of active-site residues in the dealkylation reaction in the P S C S diastereomer of 2-(3,3-dimethylbutyl)methylphosphonofluoridate (soman)-inhibited Torpedo californica acetylcholinesterase (AChE) was investigated by full-scale molecular dynamics simulations using CHARMM : 400 ps equilibration was followed by 150-200 ps production runs with the fully solvated tetracoordinate phosphonate adduct of the wild-type, Trp84Ala and Gly199Gln mutants of AChE. Parallel simulations were carried out with the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…74 Enyedy et al studied continued reaction under organophosphorus inhibition with CHARMM. 75 In a series of articles from the same group, Henchman et al used MD to model water in and around AChE, 76,77 Kua et al employed a combined MD and multiple docking approach to study enzyme binding specificity with native and mutated AChE, 78,79 and Bui et al used MD to show ligand barrier crossing within the active-site gorge. 80 Zhang et al determined the structures and charges of the TS and the reactant with QM/ MM calculations.…”
Section: Carboxylic Ester Bond Hydrolysismentioning
confidence: 99%
“…74 Enyedy et al studied continued reaction under organophosphorus inhibition with CHARMM. 75 In a series of articles from the same group, Henchman et al used MD to model water in and around AChE, 76,77 Kua et al employed a combined MD and multiple docking approach to study enzyme binding specificity with native and mutated AChE, 78,79 and Bui et al used MD to show ligand barrier crossing within the active-site gorge. 80 Zhang et al determined the structures and charges of the TS and the reactant with QM/ MM calculations.…”
Section: Carboxylic Ester Bond Hydrolysismentioning
confidence: 99%
“…Moreover, the residual catalytic activity seen for a complex of AChE with the gorge-capping mamba venom toxin, fasciculin , can maybe be explained by molecular breathing. Later molecular dynamics studies have provided further evidence of loop movements creating doors for product exit . In contrast, much evidence has suggested that conformational changes are not involved during substrate hydrolysis.…”
mentioning
confidence: 99%